Evaluasi Dampak Penggunaan Lahan Di Kawasan Sekitar Mangrove Terhadap Perubahan Luasan Mangrove (Studi Kasus pada Tahura Ngurah Rai Bali) - Widnyana, I Made Alit; Bela, Riyani; Husnayaen, Husnayaen (FKIP Universitas Palangka Raya, 2024)
In Indonesia, particularly in Denpasar City, Bali, mangrove forests play a crucial role in maintaining environmental and local economic sustainability. However, in recent years, mangrove forests in Bali, as well as throughout Indonesia, have faced significant pressure due to human activities such as urban development, sand mining, and climate change. The objective of this research is to identify the dominant land use patterns around the Ngurah Rai Bali Forest Park (Tahura Ngurah Rai Bali) mangrove area and evaluate the impact of land use on mangrove area changes for the sustainability of the mangrove ecosystem in Tahura Ngurah Rai Bali. The research methodology employed in this study is descriptive. Located strategically along the Sanur, Benoa, Tuban, and Nusa Dua tourist route along the Ngurah Rai Bali bypass, Tahura Ngurah Rai Bali is geographically positioned between 8°04'2'' - 8°04'9'' south latitude (LS) and 110°50'9'' - 110°50'14'' east longitude (BT). The Long-Term Management Plan, documented and approved by the Directorate General of Conservation and Natural Resources of the Ministry of Environment and Forestry of the Republic of Indonesia through Decree SK.53/KSDAE/PKK/KSA.0/3/2023, is effective for 10 years from 2023 to 2032. This plan is an extension of the 2012-2022 Long-Term Development Plan (RPJP). The mangrove conservation area covers 159.44 hectares, while the production forest that can be converted covers 169.5 hectares. The impact of land use for purposes beyond forestry does not significantly affect the mangrove ecosystem. However, there is a highly significant impact on changes in mangrove area due to land conversion for physical structures such as the Bali Mandara Toll Road, the PT. Perusahaan Listrik Negara (PLN) Tower, and the Wastewater Treatment Plant (IPAL).